1991
DOI: 10.1007/bf02921752
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic activity of cellulase adsorbed on cellulose and its change during hydrolysis

Abstract: Hydrolysis of pure cellulose Avicel has been carried out, using Meicelase from Trichoderma viride, where the enzymatic activity of cellulase adsorbed on cellulose and its changes during the hydrolysis were investigated. A rapid drop of the hydrolysis rate during the reaction, that is always observed in enzymatic hydrolysis of cellulose, could be explained by a decline of specific activity of adsorbed enzyme, and it was implied that the decline results from a loss of synergistic action between endoglucanase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 14 publications
4
37
0
1
Order By: Relevance
“…Those authors found an empirically determined value of n equal to 5.3, indicative of the very strong decline in rate with increasing conversion and in general agreement with direct specific activity measurements (Nutor and Converse, 1991;Ooshima et al, 1991). Semimechanistic models with respect to substrate (only), involve concentration as the only substrate state variable and two or more solubilizing activities.…”
Section: Semimechanistic Modelssupporting
confidence: 63%
“…Those authors found an empirically determined value of n equal to 5.3, indicative of the very strong decline in rate with increasing conversion and in general agreement with direct specific activity measurements (Nutor and Converse, 1991;Ooshima et al, 1991). Semimechanistic models with respect to substrate (only), involve concentration as the only substrate state variable and two or more solubilizing activities.…”
Section: Semimechanistic Modelssupporting
confidence: 63%
“…The extent to which cellulases can adsorb to cellulose within a lignocellulosic substrate should provide some indication of digestibility. Previous studies have observed correlations between cellulose hydrolysis rates and bound enzyme concentrations Ooshima et al, 1991). However, earlier work examining the relationship between bound cellulase and substrate digestibility have been limited by the complexity of the cellulase system Ooshima et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, advances in cloning technologies and purification procedures have allowed the use of purified enzymes to distinguish between enzyme and substrate effects in the experiments (Eriksson et al, 2002;Palonen et al, 2004). Additionally, determining bound enzyme fractions in the reactions has become more direct and quantitative, using known extinction coefficients of the well-characterized and carefully purified enzyme components instead of indirect activity based (Meunier-Goddik et al, 1999) or colorimetric methods (Ooshima et al, 1991). However, determining the bound enzyme fraction on biomass is further complicated by the absorbance contributions of various soluble components in biomass (Ucar and Fengel, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, due to the significant need for improved enzyme activity, and the demonstrated effective action of protein and surfactant-based enzyme stabilizers, we review the different mechanisms of action of these additives on cellulase stabilization. Enhanced catalytic activity of cellulase with surfactants has been reported for a variety of substrates, including steam exploded spruce, lodgepole pine [27,[30][31][32], sigma cell 100 and steam exploded poplar [32], newspaper [33], Avicel and tissue paper [34], dilute sulfuric acid pretreated creeping wild ryegrass [29], Douglas fir exploded with SO 2 and ammonia freeze explosion (AFEX) pretreated corn stover, dilute acid pretreated corn stover [26,35], lime and ammonia recycled percolation (ARP) pretreated corn stover [26], extrusion pretreated corn stover and prairie cord grass [36,37].…”
Section: Introductionmentioning
confidence: 99%